An ecological study of COVID-19 outcomes among Florida counties - Sobur Ali; Taj Azarian (BMC Public Health, 2025)
Abstract Background During the COVID-19 pandemic, Florida reported some of the highest numbers of cases and deaths in the US; however, county-level variation in COVID-19 outcomes has yet to be comprehensively investigated. The present ecological study aimed to assess correlates of COVID-19 outcomes among Florida counties that explain variation in case rate, mortality rate, and case fatality rate (CFR) across pandemic waves. Method We obtained county-level administrative data and COVID-19 case reports from public repositories. We tested spatial autocorrelation to assess geographic clustering in COVID-19 case rate, mortality rate, and CFR. Stepwise linear regression was employed to investigate the association between COVID-19 outcomes and 17 demographic, socioeconomic, and health-related county-level predictors. Results We found mortality rate and CFR were significantly higher in rural counties compared to urban counties, among which significant differences in vaccination coverage were also observed. Multivariate analysis found that the percentage of the population aged over 65 years, the percentage of obese people, and the percentage of the rural population were significant predictors of COVID-19 case rate. Median age, vaccination coverage, percentage of people who smoke, and percentage of the population with diabetes were significant influencing factors for CFR. Importantly, higher vaccination coverage was significantly associated with a reduction in case rate (R = -0.26, p = 0.03) and mortality (R = -0.51, p < 0.001). Last, we found that spatial dependencies play a role in explaining variations in COVID-19 CFR among Florida counties. Conclusion Our findings emphasize the need for targeted, equitable public health strategies to reduce disparities and enhance population resilience during public health crises.